Discovery of noscapine derivatives as potential β-tubulin inhibitors. Issue 20 (15th October 2020) - Nemati, Faezeh; Salehi, Peyman; Bararjanian, Morteza; Hadian, Nasim; Mohebbi, Maryam; Lauro, Gianluigi; Ruggiero, Dafne; Terracciano, Stefania; Bifulco, Giuseppe; Bruno, Ines
Graphical abstract: Highlights: Twenty novel 1, 2, 3-triazole noscapine derivatives were synthesized. Selected triazoles exhibited lower cell viability compared with noscapine. Two promising compounds (8h and 9c ) were identified. The cytotoxicity was supposed to be correlated with tubulin affinity. Abstract: Twenty novel 1, 2, 3-triazole noscapine derivatives were synthesized starting from noscapine by consecutive N -demethylation, reduction of lactone ring, N -propargylation and Huisgen 1, 3-dipolar cycloaddition reaction. In order to select the most promising molecules to subject to further biophysical and biological evaluation, a molecular docking analysis round was performed using noscapine as reference compound. The molecules featuring docking predicted binding affinity better than that of noscapine were then subjected to MTT assay against MCF7 cell line. The obtained results disclosed that all the selected triazole derivatives exhibited a remarkably lower cell viability compared to noscapine in the range of 20 μM in 48 h. In an attempt to correlate the biological activity with the ability to bind tubulin, the surface plasmon resonance (SPR) assay was employed. Compounds 8a, 8h, 9c, 9f and 9j were able to bind tubulin with affinity constant values in the nanomolar range and higher if compared to noscapine. Integrating computational predictions and experimental evaluation, two promising compounds (8h and 9c ) were identified, whose relevant cytotoxicity was supposed to be correlated with tubulin binding affinity. These findings shed lights onto structural modifications of noscapine toward the identification of more potent cytotoxic agents targeting tubulin.